78 First year experience of a dedicated "radial lounge" for patients undergoing elective percutaneous coronary procedures. (9th June 2011) - Brewster, S; Weerackody, R; Khimdas, K; Little, A; Cleary, N; Penswick, A; Rothman, M; Archbold, A
Abstract : Introduction: The potential to achieve safe early mobilisation and same day discharge on a consistent basis after radial artery access has provided us with the opportunity to make a step change in the way we deliver elective care to patients undergoing percutaneous coronary procedures. We designed a dedicated "radial lounge" to accommodate patients before and after their procedure with the aim of minimising the feeling of "hospitalisation" that accompanies most encounters with health services. The lounge is a day case unit that has no beds, only chairs, and televisions but no cardiac monitors. Patients remain in their clothes throughout their hospital visit. Here we report our first year′s experience of this facility. Methods: The study population comprised all patients who attended the radial lounge between July 2009–June 2010 for coronary angiography or percutaneous coronary intervention (PCI). Patients were suitable for the radial lounge if they were elective cases who had a satisfactory radial pulse and no pre-procedure contraindication to same day discharge. Patients were excluded if they had any of the following: an unsuitable radial pulse, planned femoral access, prior coronary artery bypass surgery, or the requirement for an overnight hospital stay for planned complex/high risk PCI, renal impairment, or social reasons. The final decision regarding route of arterial access was left to the operator. Results: In the one year study period, 1548 patients were managed in the radial lounge. 1109 patients underwent coronary angiography, 114 (10.2%) of whom also had a pressure wire or intravascular ultrasound, and 439 underwent PCI. This represented approximately 88% of our unit′s elective angiograms and 60% of our elective PCIs. Among the patients who underwent angiography, 938 (84.5%) were performed radially and 1076 (97.0%) were discharged from the radial lounge on the same day as their procedure. Among the PCI patients, 359 (81.8%) were performed radially and 372 (84.7%) were discharged the same day. The PCI group included 326 (74.3%) patients who had a single vessel treated, 105 (23.9%) who had two vessels or a bifurcation with a significant side branch treated, and 8 (1.8%) patients who had three vessels treated. There were no deaths or arrhythmias in the radial lounge. Requirement for overnight admission was significantly more common after femoral access compared with radial access for both angiography (4.1% vs 2.8%; p<0.05) and PCI (21.3% vs 14.2%; p<0.01). Conclusions: A dedicated radial lounge free of cardiac monitors is a safe environment in which to manage most patients before and after elective coronary angiography and PCI. The lack of monitoring necessitates patient selection but this does not prevent the lounge being suitable for the majority of elective patients. Femoral access is associated with a significantly greater requirement for overnight admission.